Pengaruh Mobile Banking Dan Loan To Deposit Ratio Terhadap Return On Asset - Riska Dwi Maharani (Jurnal Akuntansi dan Keuangan, 2023)
This study's goal is to determine the impact of mobile banking and loan-to-deposit ratio (LDR) on the return on investment (ROA) of traditional banks listed on the Indonesian Stock Exchange for the period 2018-2022. is. The study population consists of traditional banks that registered up to 46 companies in his IDX during the period 2018-2022. In this study, random or side sampling methods were used as sample methodologies. The study used a sample of 30 traditional banking companies listed on the IDX for the period 2018-2022. Secondary data from the company's annual report was used in this analysis. The data analysis technique used in this study is multiple regression analysis. The findings of this study demonstrate how loan-to-deposit ratio (LDR) and mobile banking have an impact on return on investment (ROA).